Wpływ komponentów organicznych na zmiany właściwości rekultywowanych gleb leśnych na siedlisku boru suchego - Królak, Elżbieta; Kot, Barbara; Powalska, Ewelina; Sterniczuk, Karol; Troć, Aneta; Zychowicz, Ewelina (Leśne Prace Badawcze, 2017)
The main objective of the study was to analyse the influence of compost produced from urban green waste, sewage sludge from municipal treatment plants and horticultural peat on changes of selected chemical and microbiological parameters of forest soil reclaimed after a fire. Soil samples were collected one and two years after the components had been applied to the soil. The results from experimental sites were compared with those from control samples. In the soil samples the following parameters were determined: content of carbon and nitrogen, reaction, hydrolytic acidity and the total amount of alkaline cations. Also the total number of bacteria and fungi, including moulds and yeast, was analysed. A year after components application, pH and the number of yeasts and moulds in the soil increased. After two years the content of nitrogen and the total number of bacteria in the soil increased as well. The most beneficial effect on changes in soil properties had the application of sewage sludge, which manifested itself in a decrease of the C/N ratio. This indicated the suitability of sewage sludge in reclamation of poor forest habitats. Peat underwent the slowest mineralization among all the organic components applied to the soil.